Thermal conductivity of nonwoven needle-punched geotextiles: effect of stress and moisture. Issue 2 (19th April 2021) - Lahoori, M.; Rosin-Paumier, S.; Stoltz, G.; Jannot, Y.
Abstract : This paper explores the use of geotextiles as insulation material for energy geostructures made of compacted soil. This work is based on measurements of the thermal conductivity of four nonwoven needle-punched geotextiles of varying thicknesses made from virgin or recycled fibres. These values were measured using the hot-plate method. Then, to assess the use of these geotextiles under a covering soil layer, compression tests were performed. For each sample, the relation between thickness and vertical stress was thus established. The thermal conductivities varied from 0.04 to 0.06 W/m/K depending on the geotextile type and the compression stress applied. Subsequent measurements focused on the thermal conductivity of a bilayer compacted soil plus geotextile. Results revealed a water migration towards the geotextile and therefore a larger thermal conductivity. These results highlighted the main importance of compression load and moisture environment in the use of geotextiles as insulation products.